Comparative Analysis of Returns and Volatility Between Physical Gold and Gold Mining Stocks Listed on the Indonesia Stock Exchange During the 2020–2026 Period - Irwin Ananta Vidada; Saridawati Saridawati; Raden Muhammad Tedy Aliudin; Agung Suprianto; Etika Sabariah (Jurnal Price : Ekonomi dan Akuntasi, 2026)
Global economic uncertainty during the 2020–2026 period has generated significant volatility across investment assets, making the selection between physical gold and gold mining stocks increasingly important for investors. This study aims to compare the returns and risk (volatility) of physical gold (XAU/IDR) with four major gold mining companies listed on the Indonesia Stock Exchange (IDX), namely PT Aneka Tambang Tbk (ANTM), PT Bumi Resources Minerals Tbk (BRMS), PT Hartadinata Abadi Tbk (HRTA), and PT J Resources Asia Pasifik Tbk (PSAB). A quantitative descriptive approach with a comparative design was employed. Secondary data consisting of monthly closing prices collected during the observation period were analyzed using descriptive statistical techniques to evaluate the performance characteristics of each investment instrument. The results indicate that all investment instruments generated positive returns, although with substantially different performance characteristics. Physical gold produced a stable return of 299.64% with a very low level of risk, reflecting its role as a conservative investment asset. In contrast, gold mining stocks achieved a considerably higher average return of 724.53%, with BRMS recording the highest return of 1,411.11%. However, these higher returns were accompanied by substantially greater risk, as reflected by a standard deviation of 607.41%. The findings suggest that operating leverage in gold mining companies amplifies return potential while simultaneously increasing investment risk. Overall, physical gold is more suitable as a safe-haven and wealth preservation instrument, whereas gold mining stocks are better suited for aggressive wealth accumulation strategies targeting investors with a high risk tolerance and long-term capital growth objectives.